Zastosowanie controllingu w zakładach opieki zdrowotnej szansą na lepszą przyszłość - Gubernat, Ewa (Controlling and its Role in the Future of Health Care Service, 2006)
There is one of basic instrument of forceful management Controlling. Meaning is more great within last years. They take advantage it presently already not only private, commercial enterprises but outposts of medical custodies also. As it is related with sphere of effective management controlling, it must be inscribed to each range of basic operation of hospital. Forceful management means canvass of new contract in practice for hospitals, achievement financial plans indicated and development steady.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 193-202